1997
DOI: 10.1111/1467-8543.00073
|View full text |Cite
|
Sign up to set email alerts
|

Trends in the Training of Male and Female Workers in the United Kingdom

Abstract: After controlling for the effect of impact of human capital and other characteristics, including whether respondents are interviewed directly or by proxy, there has been a convergence in the experience of women and men regarding access to training in Britain. This convergence applies both to total training participation in any four weeks and to the weekly volume of off-thejob training.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
33
1
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 2 publications
4
33
1
1
Order By: Relevance
“…Conversely, the proportion of female employees in the establishment has a significant negative impact on establishment training. This finding contrasts with recent evidence by Green and Zanchi (1997) but is consistent with the findings of Booth (1997), andBooth (1991) using British data.…”
supporting
confidence: 78%
See 1 more Smart Citation
“…Conversely, the proportion of female employees in the establishment has a significant negative impact on establishment training. This finding contrasts with recent evidence by Green and Zanchi (1997) but is consistent with the findings of Booth (1997), andBooth (1991) using British data.…”
supporting
confidence: 78%
“…Green and Zanchi, 1997). This catch-up of women in training, from an earlier position in which men had greater access, is associated with the growing participation of women in the labour market and the changing composition of occupations.…”
Section: Training and Establishment Survivalmentioning
confidence: 99%
“…Numerous empirical results have shown that, in general, males participate more in organizational training than women (see Feinberg and Halperin 1978;Green 1993;Green and Zanchi 1997;Lepage 1999;Veum 1993). A possible explanation for this effect lies in the segmentation market theory.…”
Section: Gendermentioning
confidence: 99%
“…In the case of training for employees, male entrepreneurs are expected to pursue long-term growth of their firms compared with female entrepreneurs, and thus, may tend to feel more strongly about providing training opportunities for their employees. According to Ng's (2005) review, it has been well documented in UK studies that the probability of receiving training decreases as an individual ages (Green & Zanchi, 1997;Greenhalgh & Mavrotas, 1996;Oosterbeek, 1996), as well as in a US study (Barron et al, 1997) and an Australian study (Miller, 1994). The human capital theory provides support for these results.…”
Section: Entrepreneurial Characteristicsmentioning
confidence: 95%